Effects of evidence-based perineal massage on maternal and neonatal physiological outcomes and childbirth experience in primiparous women: A quasi-experimental study - Yuxuan Li; Linlin Cao; Hongxiao He; Haishan Wei; Hong Lu; Shenglian Ni; Jie Lu; Ruiqing Dong; Mengting Wang; Xiaoding Zhou (Next Research, 2026)

High-Precision Surfacing Position Prediction for Underwater Gliders via Coordinate Transformation - Yaojian Zhou; Mengjiao Kang; Jiancheng Yu; Jisong Bai; Tong Xue; Xiaoding Cheng (Journal of Marine Science and Engineering, 2025)
The accurate prediction of the surfacing position of underwater gliders (UGs) is critical for mission success and cost-effective retrieval. However, current state-of-the-art (SOTA) methods often rely on complex multi-model integrations or large volumes of ocean current data, thereby increasing operational costs and system complexity. In this study, we systematically introduce—for the first time—a coordinate-transformation-based prediction framework, originally applied in other navigation contexts, into the UG surfacing-position-prediction task. By projecting both the glider’s entry and surfacing positions into a Universal Transverse Mercator (UTM) planar coordinate system and treating the resulting displacement as the prediction target, we avoid dependence on heavily parameterized current models, simplify the training process, and maintain robust predictive accuracy. Our approach combines common machine learning predictors (e.g., AdaBoost, LGBM, gradient boosting, random forest, decision trees) instead of advanced deep learning architectures, thus reducing computational overhead. Experiments on two real-world sea trial datasets (containing 2159 and 1456 profiles, respectively) show that, compared with direct regression approaches, this method improves positioning accuracy by up to 50% within a 500-meter range, yet requires minimal multi-source data. Overall, this study integrates the concept of coordinate transformation into the task of predicting the surfacing position of underwater gliders, effectively streamlining the method without sacrificing accuracy. The result is a highly flexible and cost-effective approach, providing theoretical support for future optimizations of underwater glider navigation systems.

Large-scale genomic and phenomic analyses of modern cultivars empower future rice breeding design - Xiaoding Ma; Hao Wang; Shen Yan; Chuanqing Zhou; Kunneng Zhou; Qiang Zhang; Maomao Li; Yaolong Yang; Danting Li; Peng Song; Cuifeng Tang; Leiyue Geng; et al. (Molecular Plant, 2025)

Correction to: An Innovative Mechanism of Directional Rock Cracking Mechanics and Mine Pressure Control Method for Energy-Gathering Blasting - Xiaoding Xu; Yuejin Zhou; Jun Yang; Yubing Gao; Chun Zhu; Yajun Wang; Qiang Fu (Rock Mechanics and Rock Engineering, 2024)

An Innovative Mechanism of Directional Rock Cracking Mechanics and Mine Pressure Control Method for Energy-Gathering Blasting - Xiaoding Xu; Yuejin Zhou; Jun Yang; Yubing Gao; Chun Zhu; Yajun Wang; Qiang Fu (Rock Mechanics and Rock Engineering, 2024)

Nano-enabled seed treatment: A new and sustainable approach to engineering climate-resilient crops - Lijuan Zhao; Xiaoding Zhou; Zhao Kang; Jose R. Peralta-Videa; Yong-Guan Zhu (Science of The Total Environment, 2024)

Thermal treatment of municipal solid waste incineration fly ash and nanofiltration membrane concentrate co-processing: Speciation of chromium and its leachability - Qian Wu; Zongru Wu; Hao Wu; Qingxu Wang; Nannan Huang; Jieya Zhou; Xiaoding Li; Lihu Shi; Shulei Tian; Meitong Li (Journal of Cleaner Production, 2023)

Investigation of Instability and Blasting Caving Technology of Composite Support Structure in the Goaf of Gypsum Mine - Pang Shun; Xiaoding Xu; Yuejin Zhou; Guchun Zang; Jun Wang (Geotechnical and Geological Engineering, 2021)

Comparative analysis of genetic diversity of rice (Oryza sativa L.) varieties cultivated in different periods in China - Ruyu Tang; Di Cui; Jian Zhou; Wenqiu Li; Xiaoding Ma; Bing Han; Xiaohong Guo; Zhengwu Zhao; Longzhi Han (Genetic Resources and Crop Evolution, 2021)

DNA Mismatch Repair Deficiency Detection in Colorectal Cancer by a New Microsatellite Instability Analysis System - Shafei Wu; Xiaoding Liu; Jing Wang; Weixun Zhou; Mei Guan; Yuanyuan Liu; Junyi Pang; Tao Lu; Liangrui Zhou; Xiaohua Shi; Huanwen Wu; Zhiyong Liang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2020)
Background Although microsatellite instability (MSI) is most commonly detected in colorectal cancer (CRC), improvement in MSI analysis method can always help us better assessing MSI phenotypes and gaining useful information in challenging cases. The purpose of current study is to explore whether the ProDx® MSI analysis System (ProDx® MSI) can improve MSI classification in CRC. Methods We compared the MSI profiles of 97 FFPE samples from CRC patients by ProDx® MSI with Promega MSI analysis System 1.2 and NCI panel. The result is then confirmed by IHC test, which evaluate MMR protein expression. Furthermore, next generation sequencing was performed to double confirm the specimens with discordant results. Results Among the total 97 CRC cases, 35 were scored as MSI-High by ProDx® MSI, Promega MSI analysis System 1.2, and NCI panel simultaneously. Three extra MSI-High cases were identified by ProDx® MSI. These three cases were classified as MSI-Low by NCI panel, while two of these as MSI-Low, and 1 as MSS by Promega MSI analysis System 1.2. ProDx® MSI had higher concordance with IHC detection compared with Promega MSI Analysis System 1.2 and NCI panel at 99.0%, 96.9%, and 95.9%, respectively. The ProDx® MSI distinguished MSI status with 100% sensitivity and 98.4% specificity. Our data showed that MSI-High phenotype occurred most frequently in tumor development stage I and stage II. Conclusions The colorectal cancer can be classified according to MSI status accurately by ProDx® MSI. More cases with MSI-High feature may be revealed by ProDx® MSI than by previous test systems in colorectal cancer.

Climate analysis of tornadoes in China - Yeqing Yao; Xiaoding Yu; Yijun Zhang; Zijiang Zhou; Wusan Xie; Yanyu Lu; Jinlong Yu; Lingxiang Wei (Journal of Meteorological Research, 2015)

A knockdown mutation of YELLOW-GREEN LEAF2 blocks chlorophyll biosynthesis in rice - Hong Chen; Zhijun Cheng; Xiaoding Ma; Han Wu; Yanling Liu; Kunneng Zhou; Yilin Chen; Weiwei Ma; Jingcui Bi; Xin Zhang; Xiuping Guo; Jiulin Wang; et al. (Plant Cell Reports, 2013)

BEAK LIKE SPIKELET1 is Required for Lateral Development of Lemma and Palea in Rice - Xiaoding Ma; Zhijun Cheng; Fuqing Wu; Mingna Jin; Liguo Zhang; Feng Zhou; Jiulin Wang; Kunneng Zhou; Jian Ma; Qibing Lin; Cailin Lei; Jianmin Wan (Plant Molecular Biology Reporter, 2013)